HILANG PANAS ALAMIAH DAERAH MANIFESTASI PANAS BUMI UNTUK ESTIMASI POTENSI SUMBER DAYA SPEKULATIF ENERGI PANAS BUMI DISEKITAR GUNUNG TAMPUSU - Almasih Mayumi Rontos; Rolles Nixon Palilingan; Cyrke A. N. Bujung (Fakultas Matematika Ilmu Pengetahuan Alam dan Kebumian, Universitas Negeri Manado, 2021)
Geothermal energy is one of the new and renewable alternative energy sources that are environmentally friendly. Indonesia is one of the countries in the world that has large geothermal reserves. The appearance of a manifestation that appears to the surface indicates the potential for geothermal energy in an area. This study aims to calculate the amount of natural heat loss to determine the potential of speculative resources. Research using natural heat loss calculations is the initial stage in starting geothermal exploration. In the area around Mount Tampusu, Remboken District, Minahasa Regency, North Sulawesi Province, there are surface manifestations that can be seen from the heat loss and speculative resources. This research was conducted by taking data in the field and processing the data using the natural heat loss equation in each manifestation. Based on the research results, the total natural heat loss in manifestations around Mount Tampusu is 17,16 mW and the speculative resources are 171,6 mW.